Photocatalyst film-bearing substrate and water-splitting device including the same

By setting up a photocatalytic film on the substrate and using a base film and adhesive, the problem of unfixed photocatalytic particles is solved, and the stability of the photocatalytic water cracking device and the improvement of hydrogen supply are achieved.

JP2025020019APending Publication Date: 2025-02-07NIPPON SHEET GLASS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024114429
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2024-07-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, there are few researches on the technology of fixing photocatalytic particles to the substrate, which leads to insufficient durability of the photocatalytic water cracking device and it is difficult to stabilize the supply of hydrogen.

Method used

A photocatalytic film is provided on the substrate, and the durability of the photocatalytic film is improved by adding a base film between the substrate and the photocatalytic film, and contacting the photocatalytic particles using a binder.

Benefits of technology

It improves the stability of the photocatalytic water cracking device and the hydrogen supply capacity, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020019000001_ABST
    Figure 2025020019000001_ABST
Patent Text Reader

Abstract

To improve a photocatalyst film-bearing substrate for use in a water-splitting device.SOLUTION: A photocatalyst film-bearing substrate 10 includes a substrate 1, a photocatalyst film 2, and a primer layer 3 disposed between the substrate 1 and the photocatalyst film 2. The photocatalyst film 2 includes photocatalyst particles, which can exhibit photocatalytic activity to produce gas from water upon light irradiation, and a binder in contact with the photocatalyst particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a substrate with a photocatalytic film, and further to a water splitting device using the substrate with a photocatalytic film. [Background technology]

[0002] Hydrogen production technology that uses photocatalysts to split water has attracted attention. This is because hydrogen production technology that directly splits water using light energy could potentially become a technology for supplying inexpensive hydrogen on a large scale. Various photocatalyst particles have been developed to pursue this possibility. For example, Non-Patent Document 1 discloses a photocatalyst in which a co-catalyst is selectively introduced into specific crystal planes of Al-doped SrTiO3 particles. This photocatalyst particle is capable of splitting water with a quantum yield of nearly 100% to produce hydrogen and oxygen. Patent Document 1 also discloses photocatalyst particles in which a co-catalyst different from that in Non-Patent Document 1 is supported on Al-doped SrTiO3 particles. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Nature, 2020, vol.581, pp.411-414 [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2023-88059 Summary of the Invention [Problem to be solved by the invention]

[0005] To date, development efforts in hydrogen production technology have focused primarily on improving photocatalytic particles. However, to the inventors' knowledge, little progress has been made on technology for fixing photocatalytic particles to substrates. Therefore, the present invention aims to provide a new photocatalytic film-coated substrate that could become a key device in water splitting apparatuses. [Means for solving the problem]

[0006] In order to stably supply hydrogen, it is desirable to extend the usable life of a water splitting apparatus. As a result of investigations from the perspective of extending the usable life, the present inventors found that there was room for improvement in the durability of a photocatalyst film-coated substrate that is continuously exposed to water and generated gases during the operation of a water splitting apparatus, and thus completed the present invention.

[0007] The present invention provides A substrate, a photocatalytic film, and an undercoat film disposed between the substrate and the photocatalytic film, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles, thereby providing a photocatalyst film-attached substrate.

[0008] The present invention also provides a water splitting apparatus comprising the photocatalyst film-coated substrate of the present invention. [Effects of the Invention]

[0009] According to the present invention, a photocatalytic film-coated substrate and a water splitting apparatus suitable for stably supplying hydrogen are provided. [Brief explanation of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a substrate with a photocatalytic film. [Figure 2] FIG. 1 is a partial cross-sectional view showing an example of a water decomposition apparatus. [Figure 3] 1 is a graph showing the results of a hydrogen generation test measured in an example. [Figure 4]FIG. 2 is a diagram showing the results of observing the cross section of a substrate with a photocatalyst film produced in an example using a scanning electron microscope (SEM). [Figure 5] FIG. 2 is a diagram showing the results of SEM observation of a cross section of a substrate with a photocatalyst film produced in an example. DETAILED DESCRIPTION OF THE INVENTION

[0011] The present invention will be described in detail below, but the following description is not intended to limit the present invention to a specific embodiment.

[0012] The present invention provides a photocatalyst film-coated substrate and a water splitting apparatus having the following configurations. The first form is A substrate, a photocatalytic film, and an undercoat film disposed between the substrate and the photocatalytic film, The photocatalyst film is a photocatalyst film-attached substrate that includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles.

[0013] In the second embodiment, the photocatalytic film does not peel off from the substrate after a hot water immersion test is performed. This is a substrate with a photocatalytic film of the first type. The warm water immersion test involves immersing the photocatalyst film-coated substrate in water at 40° C. for four days.

[0014] In a third embodiment, the undercoat film has a thickness of 5 nm or more and 250 nm or less. The substrate with a photocatalytic film of the first or second embodiment.

[0015] A fourth embodiment is the photocatalyst film-attached substrate of any one of the first to third embodiments, wherein the undercoat film contains Al.

[0016] A fifth embodiment is the photocatalyst film-coated substrate of any one of the first to fourth embodiments, wherein the ratio of the photocatalyst particles to the binder in the photocatalyst film is in the range of 99:1 to 50:50 on a mass basis.

[0017] A sixth embodiment is the photocatalyst film-coated substrate of the fifth embodiment, wherein the ratio of the photocatalyst particles to the binder in the photocatalyst film is in the range of 99:1 to 80:20 on a mass basis.

[0018] A seventh embodiment is the photocatalyst film-coated substrate of any one of the first to sixth embodiments, wherein the binder contains Al.

[0019] An eighth embodiment is the photocatalyst film-attached substrate of the seventh embodiment, wherein the binder further contains Si.

[0020] A ninth form is the photocatalyst film-attached substrate of any one of the first to eighth forms, wherein the binder contains non-spherical particles, and the ratio of the major axis L1 to the minor axis L2 of the non-spherical particles is 3 or more.

[0021] A tenth aspect is the photocatalyst film-attached substrate of any one of the first to ninth aspects, wherein the substrate includes a glass plate or glass fiber.

[0022] An eleventh embodiment is a water splitting device comprising the photocatalyst film-coated substrate of any one of the first to tenth embodiments.

[0023] [Photocatalytic film substrate] FIG. 1 shows a cross section of an example of a photocatalyst film-coated substrate of this embodiment. The photocatalyst film-coated substrate 10 comprises a substrate 1 and a photocatalyst film 2 formed on the substrate 1. An undercoat film 3 is disposed between the substrate 1 and the photocatalyst film 2. In other words, the undercoat film 3 is formed in advance on the surface of the substrate 10 on which the photocatalyst film 2 is to be formed. The photocatalyst film 2 contains photocatalyst particles and a binder. The substrate, undercoat film, and photocatalyst film will be described in order below.

[0024] <Base> The substrate has the function of supporting the photocatalytic film, and there are no limitations on its shape or material as long as it can perform this function. The shape of the substrate is, for example, plate-like or container-like. A plate-like substrate may be a flat plate or a curved plate. The substrate may contain at least one selected from the group consisting of metal, resin, and inorganic compound. Specifically, the substrate may contain a resin material or a glass material, or may contain a glass material. The substrate may contain a glass plate or glass fiber. A substrate containing glass fiber may be a molded body of glass fiber, such as a glass mat or glass cloth. When the substrate contains a glass material that is prone to peeling of the photocatalytic film, application of this embodiment is likely to achieve a significant effect in preventing peeling. There are no particular limitations on the thickness of the substrate.

[0025] <Base film> The undercoat film may have the effect of suppressing peeling of the photocatalytic film. An undercoat film having such an effect can be called a peel-preventing layer. The undercoat film may contain an oxide. The undercoat film may contain at least one element selected from the group consisting of Al, Si, Ta, Nb, Ce, Zn, Ti, Mg, Zr, and Fe, or may be a film containing an oxide of such an element. From the viewpoint of suppressing peeling, the undercoat film preferably contains aluminum oxide, and more preferably has aluminum oxide as its main component. In this specification, the term "main component" refers to the component with the highest content by mass. An undercoat film containing aluminum oxide as its main component may further contain other oxides, such as silicon oxide.

[0026] Along with the undercoat film, the binder contained in the photocatalyst film can also contribute to preventing the photocatalyst particles from falling off. The placement of the undercoat film relatively reduces the amount of binder required to prevent the photocatalyst particles from falling off. A decrease in the binder ratio in the photocatalyst film can increase the ratio of photocatalyst particles, which can lead to an increase in the amount of gas generated from the photocatalyst film. The combined use of the undercoat film and binder can contribute not only to the durability of the photocatalyst film, but also to an increase in the amount of gas generated from the photocatalyst film.

[0027] The material constituting the base film may be granular or amorphous, similar to the binder described below. The granular binder is derived, for example, from a sol contained in the coating liquid for forming the photocatalytic film. The shape of the granular material may be spherical or non-spherical. It is desirable that at least a portion of the base film contains a granular material. Desirable examples of the shape and dimensions of the granular material are as described in the section explaining the binder.

[0028] The thickness of the undercoat film may be, for example, 1 nm or more and 800 nm or less, or even 2 nm or more and 500 nm or less. The thickness of the undercoat film may be 5 nm or more, or even 10 nm or more. The thickness of the undercoat film may be 400 nm or less, or even 300 nm or less. However, if the undercoat film is too thick, the contact area between the photocatalyst particles and the undercoat film increases, which may reduce the amount of gas generated from the photocatalyst film. Therefore, the undercoat film may be 250 nm or less, or even 200 nm or less. The upper and lower limit values ​​of the thickness described above can be arbitrarily combined to set the range. The undercoat film may be a single-layer film or a multi-layer film having two or more layers.

[0029] <Photocatalyst film> (Photocatalyst particles) The photocatalyst particles exhibit a photocatalytic function of generating gas from water upon irradiation with light. The generated gas may contain at least one selected from the group consisting of hydrogen and oxygen. The photocatalyst particles may have a photocatalytic function of decomposing water upon irradiation with light to generate hydrogen and oxygen. However, the photocatalyst particles may include first photocatalyst particles that generate hydrogen and second photocatalyst particles that generate oxygen. A system including the first photocatalyst particles and the second photocatalyst particles may also include a medium responsible for charge transfer. In a system including a medium responsible for charge transfer, the first photocatalyst particles generate hydrogen from water upon irradiation with light and oxidize the medium to generate its oxidized form. The second photocatalyst particles generate oxygen upon irradiation with light and reduce the medium to generate its reduced form. The reduced form becomes an oxidized form through an oxidation reaction involving the first photocatalyst particles, and then returns from the oxidized form to a reduced form through a reduction reaction involving the second photocatalyst particles.

[0030] The photocatalytic particles may contain at least one compound selected from the group consisting of oxides, oxynitrides, nitrides, and chalcogenide compounds. The photocatalytic particles may contain at least one element selected from the group consisting of Sr, Na, Mg, Al, Si, Ca, Ti, V, Fe, Cu, Zn, Ga, Y, Zr, Nb, Ag, In, Sn, Ba, La, Ta, W, and Bi.

[0031] The compounds contained in photocatalyst particles may be doped, and in some cases, a promoter may be introduced to enhance the photocatalytic function. For example, SrTiO3 may be doped with Al (SrTiO3:Al) or co-doped with Rh and Sb (SrTiO3:Rh,Sb). For example, SrTiO3:Al may support Rh / Cr2O3 as a hydrogen generation promoter and CoOOH as an oxygen generation promoter (Non-Patent Document 1). However, the promoter for SrTiO3:Al is not limited to the above, and may also be a promoter containing Co and Cr, and Ru and / or Pt, for example (Patent Document 1).

[0032] The influence of doping materials and co-catalysts on the adhesion between the photocatalytic film and the substrate is extremely limited. Hereinafter, in this specification, the types of dopants and co-catalysts will be omitted and the photocatalytic particles will be referred to. For example, the photocatalytic particles and photocatalytic materials disclosed in Non-Patent Document 1 and Patent Document 1 will be referred to as "SrTiO3 particles" and "SrTiO3," respectively.

[0033] The photocatalytic material contained in the photocatalyst particles can be a variety of compounds sometimes called optical semiconductors. The photocatalytic material generates photoexcited charges when irradiated with, for example, ultraviolet or visible light, and these charges reduce protons on the particle surface to generate hydrogen or oxidize water molecules to generate oxygen. Examples of photocatalytic materials include SrTiO3, Y2Ti2O5S2, BaTa2O5, BaTaO2N, and BaLa4Ti4O. 15 , NaTaO3, AgTaO3, AgLi 1 / 3 Ti 2 / 3O2, Ga2O3, WO3, (Cu, Ga) 0.8 Zn 0.4 S2, CuGaS2, LaMg 1 / 3 Ta 2 / 3 The photocatalytic material may include at least one selected from the group consisting of O2N, SnNb2O6, NaNbO3, Ta3N5, Sn3O4, BiVO4, Bi2MoO6, PbMO4, PbWO4, AgVO3, Ag3VO4, and La2Ti2O7. The photocatalytic material may be a composite material. For example, La2Ti2O7 may be composited with black phosphorus and gold nanoparticles.

[0034] The average particle size r1 of the photocatalyst particles may be, for example, in the range of 100 nm to 3 μm, or even 200 nm to 1 μm. The average particle size can be determined by randomly selecting 50 particles when observed with a scanning electron microscope, and averaging the maximum length (major axis) L1 that can be secured within each particle and the length (minor axis) L2 of the granular body along the axis perpendicular to the midpoint of the major axis, as the particle size of the selected particle, and then calculating the arithmetic mean value of the particle sizes of the 50 particles. Photocatalyst particles with an average particle size of 100 nm or more, or even 200 nm or more, tend to peel off easily from the substrate.

[0035] (binder) The binder has the function of suppressing peeling of the photocatalytic film from the substrate. At least a portion of the binder contacts the photocatalytic particles and can contribute to fixing the photocatalytic particles. The binder may contain at least one metal element selected from the group consisting of Al, Ta, Nb, Ce, Fe, and alkali metal elements. The alkali metal element may be at least one selected from the group consisting of Li, Na, and K. The binder may particularly contain Al and / or alkali metal elements. The binder may further contain Si as an element in addition to the at least one metal element described above, particularly Al and / or alkali metal elements. The binder may contain inorganic compounds such as oxides, oxynitrides, and nitrides, particularly oxides. However, the binder is not limited to these. The binder may also contain organic compounds such as cellulose nanofibers, or carbon atoms such as carbon nanotubes, fullerenes, and graphene. The binder may also contain glass fibers.

[0036] The form of the binder is not particularly limited, but may be granular. However, the binder may not be granular, but may be amorphous. Granular binders are derived, for example, from a sol contained in a coating liquid for forming a photocatalytic film. Amorphous binders are derived, for example, from metal alkoxides, alkali silicates, etc. in the coating liquid.

[0037] An example of the shape of a granular body is a spherical shape. In this specification, a spherical particle means a shape in which, when observed with an electron microscope such as a scanning electron microscope, the major axis of the granular body (the maximum length that can be secured within the granular body) is L1 and the length of the granular body along an axis perpendicular to the midpoint of the major axis (minor axis) is L2, L1 / L2<3 holds. Therefore, cubic particles are treated as spherical particles in this specification.

[0038] The shape of the granular material may be non-spherical. In this specification, non-spherical particles refer to a shape in which, based on the above-mentioned L1 and L2, L1 / L2≧3 holds when observed with an electron microscope such as a scanning electron microscope. Non-spherical particles may also hold L1 / L2≧5, L1 / L2≧10, or even L1 / L2≧15. Examples of the shape of non-spherical particles include rods, such as needles or columns; chains, in which granular bodies are connected in a chain; fibers; and feathers, in which multiple fibrous bodies are aggregated in a feather-like shape. The non-spherical particles may be at least one selected from the group consisting of rod-shaped particles, chain-shaped particles, fibrous particles, and feather-shaped particles. Non-spherical particles can be relatively effective in suppressing peeling of the photocatalytic film. Non-spherical particles can be introduced into the photocatalytic film, for example, using a sol containing non-spherical particles.

[0039] The average particle size r2 of the granular binder may be, for example, in the range of 10 nm to 50 nm, or even 30 nm to 50 nm. As explained for the average particle size r1 of the photocatalyst particles, the average particle size can be determined by averaging the particle sizes of 50 granules, with the average value of the long diameter L1 and short diameter L2 of the granules being the particle size of the granules. The average particle size r2 of the binder may be smaller than the average particle size r1 of the photocatalyst particles (r1>r2).

[0040] The average major axis of the non-spherical binder particles may be, for example, from 100 nm to 5 μm, or even from 100 nm to 3 μm. The average minor axis of the non-spherical binder particles may be, for example, from 1 nm to 20 nm, or even from 3 nm to 10 nm. The average major axis may be 5 to 5,000 times, or even 10 to 100 times, the average minor axis. As with the average particle size, the average major axis and average minor axis can be determined by randomly selecting 50 particles and averaging the major axis L1 and the minor axis L2 of each particle when observed with a scanning electron microscope.

[0041] It is desirable that at least a part of the binder is granular. Granular materials are relatively advantageous from the viewpoint of ensuring voids around the photocatalytic particles. In particular, when using an amorphous binder containing an alkali metal element, it is desirable to use a granular binder in combination. It is desirable that the binder contains both spherical and non-spherical granular materials.

[0042] (Ratio of photocatalyst particles to binder / Ratio of materials that make up the binder) In the photocatalytic film, the ratio of photocatalytic particles to binder may be in the range of 99:1 to 20:80, 99:1 to 50:50, or 97:3 to 50:50 by mass. The ratio of photocatalytic particles to binder may be in the range of 90:10 to 60:40. However, from the viewpoint of ensuring the amount of gas generated from the photocatalytic particles, the ratio of photocatalytic particles to binder may be in the range of 99:1 to 80:20, 97:3 to 80:20, or even 95:5 to 80:20.

[0043] The binder may include a binder A containing Al and / or an alkali metal element and a binder B containing Si. Binder A may be a binder containing Al. In this case, the ratio of binder A to binder B may be in the range of 90:10 to 5:95, or even 90:10 to 10:90, by mass. The ratio of binder A to binder B may be in the range of 40:60 to 5:95, or even 30:70 to 5:95. The ratio of binder C, which is a non-spherical granular material, to binder D, which is a spherical granular material, may also be in the range of the ratio described for binders A and B, by mass. The ratio of binder C to binder D may be, for example, in the range of 40:60 to 5:95, or even 30:70 to 5:95.

[0044] The mass of the binder in the photocatalytic film can be determined based on the compounds (e.g., Al2O3, Li2O, SiO2) of the target elements (e.g., metal elements such as Al, Li, Na, and semi-metal elements such as B and Si) in the photocatalytic film.

[0045] (Photocatalytic film thickness) The thickness of the photocatalytic film is not particularly limited, but is, for example, 1 μm or more, further 2 μm or more, and 50 μm or less, 20 μm or less, further 15 μm or less.

[0046] (Adhesion of photocatalytic film) The adhesion of a photocatalytic film to a substrate can be evaluated by a hot water immersion test or a thermal cycle test. Photocatalytic films that generate gas from water are used while immersed in water, so evaluating the adhesion in this state can provide an indicator of durability. The hot water immersion test is performed by immersing a substrate with a photocatalytic film in water at 40°C and leaving it to stand for four days. This test takes into account the fact that the water in the water splitting device may heat up due to exposure to light such as sunlight. The thermal cycle test is performed by immersing a substrate with a photocatalytic film in water and subjecting it to four cycles, with one cycle consisting of four hours at 90°C and four hours at -15°C.

[0047] (specific surface area of ​​photocatalytic film) From the viewpoint of securing a portion for generating gas, it is desirable that the specific surface area of ​​the photocatalytic film is high. For example, the specific surface area of ​​the photocatalytic film is 50 m 2 / g or more, 80m 2 / g or more, and 100m 2 / g or more, in some cases 120m 2 The upper limit of the specific surface area is not particularly limited, but may be, for example, 1000 m 2 / g or less, and 500m 2 / g or less. The photocatalytic film may be a porous film having a specific surface area of ​​the above-mentioned order.

[0048] Next, a method for producing a substrate with a photocatalyst film will be described. <Method for manufacturing a substrate with a photocatalytic film> A substrate with a photocatalyst film can be manufactured by a method including the steps of applying a coating liquid A for forming a base film onto a substrate to form a base film on the surface of the substrate, and applying a coating liquid B for forming a photocatalyst film onto the base film to form a photocatalyst film on the base film. Coating liquid A may contain an oxide sol that provides the oxide constituting the base film. Coating liquid B may contain an oxide sol that provides the oxide constituting the photocatalyst particles and the binder. Coating liquids A and B may contain an oxide precursor, such as aluminum alkoxide or silicon alkoxide, instead of the oxide sol. The solid content of the coating liquid may be, for example, 18% or more, 20% or more, or even 35% or more by mass. The upper limit of the solid content may be 70% or less. An appropriate solid content concentration ensures film homogeneity and prevents a decrease in film adhesion. The above method may further include heating the substrate after applying coating liquid A or B. The heating temperature is preferably 100 to 350°C.

[0049] [Water splitting equipment] FIG. 2 shows a cross-section of an example of a water splitting apparatus according to this embodiment. The water splitting apparatus includes a support 11, a light-transmitting body 12, and a sealant 13 that watertightly seals a gap 18 between the support 11 and the light-transmitting body 12. The gap 18 is surrounded by the support 11, the light-transmitting body 12, and the sealant 13 and is connected to the outside via two holes 16 and 17. A photocatalyst film-coated substrate 10 is disposed on the support 11 so that the surface of the photocatalyst film 2 is exposed to the gap 18. The two holes, i.e., the water inlet hole 16 and the gas outlet hole 17, are provided in the light-transmitting body 12. However, the holes 16 and 17 may be provided in other locations that connect the gap 18 to the outside of the apparatus. As shown in the figure, when light 20 is irradiated while water is introduced into the gap 18 through the hole 16, the water in contact with the photocatalyst film is decomposed to generate gas 19, which is then discharged through the hole 17. [Example]

[0050] The present invention will be described in more detail below with reference to examples and comparative examples. (Examples 1 to 6 and Comparative Examples 1 to 2) - Formation of base film Except for Comparative Examples 1 and 2, alumina sol was applied to a glass plate by spin coating and dried for 1 minute in an oven maintained at 150°C to form an undercoat film on the surface of the glass plate. The glass plate used was a float glass plate with a thickness of 3 mm. The thickness of the undercoat film was 70 nm in Examples 1, 2, and 5 and 6, 100 nm in Example 3, and 280 nm in Example 4.

[0051] Formation of photocatalytic layer A coating liquid containing photocatalyst particles was prepared. An oxide sol was blended into the coating liquid to provide a binder. The solid content of the coating liquid was controlled within the range of 40 to 50 mass %. The mass ratio of the photocatalyst particles and binder that make up the solid content was adjusted as shown in Table 1.

[0052] The photocatalyst particles used were promoter-supported photocatalysts (promoter-supported RhCrOx / SrTiO3:Al) prepared as follows. <Preparation of photocatalyst SrTiO3:Al> 33 g of strontium titanate SrTiO3 (Kojundo Chemical Laboratory) and 0.28 g of aluminum oxide Al2O3 (Sigma-Aldrich) were mixed and thoroughly mixed with 142.7 g of separately ground strontium chloride SrCl2 (Kanto Chemical, 98.0%). This was placed in an alumina crucible B5 (SSA-S, 280 mL), covered, and fired in an electric furnace at 1250°C for 48 hours. After cooling to room temperature, the sample was washed with water to obtain the photocatalyst aluminum-doped strontium titanate SrTiO3:Al.

[0053] <Preparation of cocatalyst-supported photocatalyst RhCrCoOx / SrTiO3:Al> A separable sample flask was charged with 327 mg of promoter source (Na3RhCl6·nH2O (powder) Assay(Rh) 15.3%; Mitsuwa Chemical Co., Ltd.), 5 mL of Cr(NO3)3 aqueous solution (0.192 mol / L; Kanto Chemical Co., Ltd., prepared using chromium (III) nitrate nonahydrate, purity: 98.0-103.0%), and 5 mL of Co(NO3)2 aqueous solution (0.170 mol / L; Fujifilm Wako Pure Chemical Co., Ltd., prepared using cobalt (II) nitrate hexahydrate, purity: 98.0%), and 120 mL of ultrapure water. The co-catalyst source was stirred in the flask until it was homogenous. 50 g of SrTiO3:Al was added to the mixture, and ultrasonic treatment was performed for 5 minutes while stirring using a Teflon rod. The solvent was removed from the suspension using an evaporator, and the suspension was evaporated to dryness, after which the sample was dried at 60°C. The dried sample was lightly crushed in an agate mortar, spread on a porcelain dish, and fired at 275°C for 1 hour to obtain co-catalyst-supported RhCrOx / SrTiO3:Al. The obtained co-catalyst-supported photocatalyst consisted of particles with an average particle size of approximately 250 nm.

[0054] The coating liquid was applied onto the base film using a bar coater. However, in Comparative Examples 1 and 2, the coating liquid was applied directly to the surface of the glass plate. Bar coating was performed so that the thickness of the applied liquid was approximately 20 μm. After applying the coating liquid, the glass plate was air-dried for 10 minutes and then heated at 150°C for 45 minutes. In this way, a glass plate with a photocatalytic film was obtained.

[0055] The raw materials of the undercoat film and binder used in the examples and comparative examples are as follows: The shape of the granules contained in the raw materials is written in parentheses immediately after the sol name.

[0056] [Oxide sol] <Aluminum oxide> (Base film) Alumina sol (feathery): AS-200 manufactured by Nissan Chemical Industries, Ltd. (Examples 1-2, 4-6) Alumina sol (rod-shaped): 10A manufactured by Kawaken Fine Chemicals Co., Ltd. (Example 3) (Photocatalytic film binder) Alumina sol (feathery): AS-200 manufactured by Nissan Chemical Industries, Ltd. (Examples 1 to 6, Comparative Examples 1 and 2) <Silicon oxide> (Photocatalytic film binder) Silica sol (spherical): ST-OS manufactured by Nissan Chemical Industries, Ltd. (Examples 1 to 5, Comparative Examples 1 and 2) Silica sol (spherical): ST-OYL manufactured by Nissan Chemical Industries, Ltd. (Example 6)

[0057] "AS-200" contains feather-shaped aluminum oxide particles with a minor axis of 3-5 nm and a major axis of 200-500 nm. "10A" contains columnar aluminum oxide particles with a diameter of 10 nm and a height of 50 nm. "ST-OS" contains spherical silicon oxide particles with a particle size of 9 nm. "ST-OYL" contains spherical silicon oxide particles with a particle size of 60 nm.

[0058] For each of the photocatalyst film-coated substrates obtained in the above Examples and Comparative Examples, a hot water immersion test and a thermal cycle test were carried out to evaluate the film adhesion, and the hydrogen generation rate was also measured.

[0059] (Hot water immersion test) The warm water immersion test involves immersing the photocatalytic film-coated substrate in water at 40°C for 4 days. The water temperature during the test was maintained at 40°C. The film adhesion was evaluated according to the following criteria. A: After the test, the membrane was not visually peeled off, and the nonwoven fabric (Ozu Sangyo, Bemcot, contact area 4 cm) with a load of 100 g was used. 2 ) and the film will not peel off even if you wipe the surface with it. B: After the test, the film was not visually peeled off, and the nonwoven fabric (Ozu Sangyo, Bemcot, contact area 4 cm) with a load of 100 g was 2 ) and wipe the surface of the film to remove it. C: At least a part of the film was visually peeled off after the test.

[0060] (heat cycle test) The thermal cycle test involves immersing the substrate with the photocatalytic film in water and repeating four cycles, with one cycle being 4 hours at 90°C and one being 4 hours at -15°C. The film adhesion was evaluated according to the following criteria. A: After the test, the film is not peeled off visually, and the film does not peel off when the surface is lightly wiped. B: After the test, the film is not peeled off visually, but the film peels off when the surface is lightly wiped. C: At least a part of the film was visually peeled off after the test.

[0061] (Hydrogen generation test) The substrate with the photocatalyst film was placed in a reaction vessel made of PEEK resin, and an O-ring was placed in the reaction vessel to prevent the reaction water and generated gas from leaking. Next, a 2 mm thick synthetic quartz window plate was placed on top of the O-ring, a metal frame was attached to the outer periphery of the synthetic quartz window plate, and the window plate was fixed to the reaction vessel with bolts. At this time, the gap between the window plate and the surface of the photocatalyst-coated substrate was adjusted to 1 mm. Water (ion-exchanged water) was supplied into the assembled reaction vessel, and after confirming that no water was leaking from the reaction vessel, ultraviolet LED light (wavelength 365 nm, 100 mW / cm) was applied. 2 The flow rate of the generated hydrogen-oxygen mixed gas was measured using a soap film flowmeter to determine the hydrogen generation rate.

[0062] The results are summarized in Table 1. The hydrogen generation rate in the table is the value measured 21 hours after the start of measurement.

[0063] [Table 1]

[0064] It can be seen from Table 1 that the formation of the undercoat film improved the adhesion of the photocatalytic film. Furthermore, in Example 6, a relatively high hydrogen generation rate was measured, even though the ratio of photocatalytic particles was slightly lower than in Comparative Example 2. In view of these results, the placement of the undercoat film is more advantageous in terms of increasing the hydrogen generation rate than when the adhesion of the film is improved by relying only on the binder.

[0065] A hydrogen generation test was conducted over a longer period on the photocatalytic film-coated substrate obtained in Example 3. The results are shown in Figure 3. Hydrogen was generated at a stable rate over a long period from the photocatalytic film having an undercoat film and a binder. Figure 3 also shows the results of a long-term hydrogen generation test conducted on a photocatalytic film-coated substrate prepared as a reference example, without forming an undercoat film, and with an increased amount of aluminum oxide binder in the photocatalytic film, as in Comparative Example 2. In the reference example, the hydrogen generation rate gradually decreased over time, indicating that the undercoat film can contribute to stabilizing the hydrogen generation rate over the long term. Note that in the hydrogen generation test, the hydrogen generation rate was somewhat unstable in the initial measurement, so Table 1 shows the results after 21 hours, and Figure 3 shows the results after approximately 20 hours.

[0066] 4 and 5 are SEM photographs of the substrate with a photocatalytic film according to Example 1. It can be seen that the photocatalytic film is a porous film with a thickness of about 20 μm, and the thickness of the base film is about 70 nm.

[0067] Next, the results of investigation into the granular material that constitutes the binder will be described. (Reference Examples 1 to 14) In the reference example, a photocatalytic film was formed directly on a substrate without forming an undercoat film. The photocatalytic film was formed in the same manner as in the examples. However, the following oxide sol was used. When rod-shaped or fibrous alumina sol was used, the heating temperature was set to 300°C.

[0068] [Oxide sol] <Aluminum oxide> Alumina sol (spherical): Nissan Chemical Co., Ltd. 520-A (Reference Examples 1 to 3) Alumina sol (feathery): Nissan Chemical AS-200 (Reference Examples 4 to 11) Alumina sol (rod-shaped): 10A manufactured by Kawaken Fine Chemicals Co., Ltd. (Reference Examples 12-13) Alumina sol (fibrous): F1000 manufactured by Kawaken Fine Chemicals Co., Ltd. (Reference Example 14) <Silicon oxide> Silica sol (spherical): Fuso Chemical Co., Ltd. PL-3H

[0069] As mentioned above, "10A" contains columnar aluminum oxide particles with a diameter of 10 nm and a height of 50 nm. "F1000" contains fibrous aluminum oxide particles with a diameter of 4 nm and a length of approximately 1400 nm. "PL-3H" contains spherical silicon oxide particles with a particle size of 35 nm.

[0070] The photocatalytic film-coated substrates obtained from each Reference Example were subjected to a hot water immersion test. The results are shown in Table 2.

[0071] [Table 2]

[0072] From Table 2, it can be seen that a binder containing non-spherical particles is suitable for ensuring the adhesion of the film.

[0073] Furthermore, the specific surface area of ​​the photocatalyst film-attached substrate obtained from the Reference Example was measured as follows. (specific surface area) The nitrogen adsorption method (BET method) was used for the measurement under the following conditions. The equipment used was a "BELSORP-mini II" manufactured by MicrotrackBell. For pretreatment, a "BELSORP-vac II" manufactured by MicrotrackBell was used. The measurement object was the photocatalytic film powder peeled off from the substrate. Pretreatment: 120℃, 8 hours in vacuum degassing Measurement method: Constant volume method ·Adsorption temperature: 77K Saturated vapor pressure: Actual measurement ·Adsorbent cross section: 0.162nm 2 Nitrogen equilibration wait time: 500 seconds

[0074] The specific surface area is 129 cm for Reference Examples 7 and 8, respectively. 2 / g, 142cm 2 / g. As in this example, the specific surface area of ​​the film tended to increase with an increase in the ratio of spherical particles. An increase in the specific surface area of ​​the film can lead to an increase in the hydrogen generation rate. A film containing both spherical and non-spherical particles is suitable for improving both the film's adhesion and the hydrogen generation rate.

[0075] Next, the results of examining binders other than alumina sol will be described. In the following reference examples, no undercoating film was formed. (Reference Examples 15-17) In these reference examples, the following alkali silicates were used instead of alumina sol. The photocatalytic film was formed in the same manner as in the examples. The hot water immersion test was also carried out in the same manner as above. The results are shown in Table 3.

[0076] [Alkali silicate] Lithium silicate: Nissan Chemical Lithium Silicate 45 [Oxide sol] <Silicon oxide> Silica sol (spherical): Fuso Chemical Co., Ltd. PL-3H

[0077] [Table 3]

[0078] The amorphous binder derived from alkali silicate is suitable as a binder that improves the adhesion of the film. In Reference Examples 15 to 17, the binder (Li2O and SiO2) derived from alkali silicate is about 87.5% SiO2 and about 12.5% ​​Li2O by mass. However, the photocatalytic film prepared using alkali silicate instead of alumina sol as the binder raw material was relatively inferior in hydrogen generation rate compared to the photocatalytic film prepared using alumina sol. [Explanation of symbols]

[0079] 1 Base 2 Photocatalytic membrane 10. Photocatalytic film-attached substrate

Claims

1. A substrate, a photocatalytic film, and a base film disposed between the substrate and the photocatalytic film, The photocatalyst film includes photocatalyst particles capable of exerting a photocatalytic action of generating gas from water upon irradiation with light, and a binder in contact with the photocatalyst particles.

2. The substrate with a photocatalyst film according to claim 1 , wherein the photocatalyst film does not peel off from the substrate after a hot water immersion test is performed. The warm water immersion test is a test in which the photocatalyst film-coated substrate is immersed in water at 40° C. for 4 days.

3. 2. The substrate with a photocatalyst film according to claim 1, wherein the undercoat film has a thickness of 5 nm or more and 250 nm or less.

4. The substrate with a photocatalyst film according to claim 1 , wherein the undercoat film contains Al.

5. 2. The substrate with a photocatalyst film according to claim 1, wherein the ratio of the photocatalyst particles to the binder in the photocatalyst film is in the range of 99:1 to 50:50 on a mass basis.

6. 6. The substrate with a photocatalyst film according to claim 5, wherein the ratio of the photocatalyst particles to the binder in the photocatalyst film is in the range of 99:1 to 80:20 on a mass basis.

7. The substrate with a photocatalyst film according to claim 1 , wherein the binder contains Al.

8. The substrate with a photocatalyst film according to claim 7 , wherein the binder further contains Si.

9. the binder comprises non-spherical particles; 2. The substrate with a photocatalyst film according to claim 1, wherein the non-spherical particles have a ratio of a major axis L1 to a minor axis L2 of 3 or more.

10. The substrate with a photocatalyst film according to claim 1 , wherein the substrate comprises a glass plate or a glass fiber.

11. A water splitting device comprising the photocatalyst film-coated substrate according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Photocatalyst for water decomposition

    JP2023088059A